INTERNALISASI NILAI NILAI MODERASI BERAGAMA PADA PENYULUH AGAMA ISLAM DALAM PERSPEKTIF SOSIOLOGI ISLAM - Islam, Muhammad Syamsuddinil (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
Religious moderation is a vital component in maintaining harmony within Indonesia's multicultural society. However, previous research has been limited in examining the internalization process of moderation values among key actors such as Islamic religious instructors. This study aims to analyze the internalization of religious moderation values among these instructors through the lens of Islamic sociology. Employing a qualitative approach, data were gathered through participatory observation and semi-structured interviews with 12 religious instructors in Pasuruan Regency, East Java, and analyzed using cognitive, affective, and psychomotor indicators. The findings indicate that a majority of instructors demonstrate strong acceptance of moderation values, including respect for religious diversity, commitment to social justice, and engagement in inclusive dialogue. Factors such as religious education, socio-cultural context, and the utilization of media and technology play significant roles in supporting the internalization process. The perspective of Islamic sociology highlights the instructors' role as agents of change who integrate religious principles with local dynamics, adapting preaching materials to fit local culture and emphasizing social solidarity (asabiyya). This study recommends enhancing instructors' capacities through context-based training, optimizing digital media for disseminating moderate content, and incorporating local values into religious education curricula. Academically, it contributes to the enrichment of Islamic sociology as a transformative framework for addressing extremism, while also serving as a policy reference for strengthening community-based religious moderation programs.